Optimizing carbon capture efficiency with direct capturing and amine: Insights from exegetic analysis - Ali Majnoon; Seyed Farhan Moosavian; Ahmad Hajinezhad (Energy Science & Engineering, 2023)
Abstract With climate change concerns on the rise, finding efficient and sustainable ways to separate carbon dioxide from industrial gas mixtures has become increasingly important. Membrane‐based gas separation technologies offer a promising solution due to their low energy consumption, low emissions, and ease of operation. In this study, we dug deep into theoretical energy consumption and practical optimization strategies for CO2 separation using such technologies. Our results showed that CO2 separation can be achieved with relatively low specific energy consumption, ranging from 0.09 to 0.27 MJe/kg CO2, depending on feed CO2 concentration. By conducting process simulations, we determined the optimal feed gas pressure and membrane surface area required to achieve a CO2 absorption ratio of 90% (mol). We also analyzed the effects of CO2 permeation and selectivity on energy consumption and membrane area, revealing that increasing both can significantly reduce energy consumption, albeit with more membrane surface area required. Using seepage flow circulation was found to be a particularly effective way to improve feed CO2 concentration and reduce energy consumption. To optimize and improve the capturing process, we conducted exergy analysis in each of the five stages of optimization, reporting Cooling Utilities (MW), Heating Utilities (MW), and Total Utilities (MW) for each step. Our results showed that in the optimal mode, Total Utilities (MW) were reported as 228.1, highlighting the potential of membrane‐based CO2 separation for carbon capture and storage applications. This study provides valuable insights and practical strategies for achieving efficient and sustainable CO2 separation.